Monitoring co-transcriptional folding of riboswitches through helicase unwinding - Jones, Christopher P. (Methods Enzymol, 2019)
In the cell, RNAs fold and begin to function as they are being transcribed. In contrast, in the laboratory, RNAs are typically studied after transcription is completed. Co-transcriptional folding can regulate the function of riboswitches and ribozymes and dictate the order of ribonucleoprotein assembly. Methods to observe and investigate RNA folding and activity during transcription are therefore desirable, yet synchronizing RNA polymerases and incorporating labels at specific sites for biophysical studies can be challenging. A recent methodological advance has been to harness highly processive, engineered ‘super-helicases’ to unwind hybrid RNA-DNA duplexes, thereby releasing the RNA 5’ to 3’. When combined with single-molecule fluorescence detection, RNA folding and concomitant activity can be studied in vitro in a manner that mimics vectorial folding during transcription. Herein, we describe methods for designing and preparing fluorescently labeled RNA-DNA duplex substrates for sequential helicase-dependent RNA folding experiments.